(untitled) (Journal of history, 2020)
In the article, the author tries to explain the history, meaning and content of the appearance of historical words and phrases that have been preserved thanks to the policies and actions of individual khans during the Golden Horde. Through them, he delves into some obscure aspects of the history of the Golden Horde as a whole and gives scientific explanations for these aspects. Explaining the origin and content of the historical words “Religion remained from Uzbek”, “The neck of the Nara (camel) was cut in Berdibek,” the author tries to show the views of the rulers of the Golden Horde in the XIII-XIV centuries on Islam and the struggle for the throne of representatives of the Batu dynasty. Whenever possible, each ruler is given a brief historical assessment. The views of every palace ruler from Batu Khan to Uzbek Khan on Islam, the bloody struggle for the throne are examined on the basis of written sources in Arabic, Persian and Turkish.